(untitled) (Emergency Care Journal, 2022)
Sunday 27th March 2022 marked 30 years of activity of the Italian Territorial Emergency Service, also known as “118”, which was officially set up in Italy on 27th March 1992 by a presidential decree, with the aim of creating a single number for sanitary emergencies that would operate 24 hours a day, seven days a week, free of charge throughout the country. [...]